Late Adulthood Personality Development - Gooh, Mo Lee (2013)
Late adulthood is generally considered to begin at about age 65. Erik Erikson suggests that this is the time it is important to find meaning and satisfaction in life. Age sixty-five is considered a milestones and the beginning of late adulthood. By this age, it is generally brings about retirement from work, eligibility for Social Security and Medicare benefits, income tax advantages, reduced fares and admission prices to leisure events, and special purchase or discount privileges.